Improving Mathematics Learning Outcomes with Problem Based Learning in Class V Students at Plesungan 2 Elementary School - Riastiani, Riastiani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
In this research action, it aims to determine the increase in students' mathematics learning outcomes in speed material using the Problem Based Learning (PBL) learning model. The method used in this study is the Pre-Experimental (Pre-Experimental Design) in the form of a Pretest-Posttest One Group Design. The subjects in this study were 5th grade SDN 02 Plesungan, totaling 16 students. The instrument used in this study is 10 multiple choice tests that are integrated with the Google form. This research data uses quantitative data. Quantitative data is in the form of pretest and posttest scores. Data analysis in this study used the Normalized gain or N-gain score test. The results of this study showed that the average pretest score was 60, and after the treatment the average value increased to 98.9. Then further analysis was carried out to produce an N-gain value of 0.98958 and an N-gain (%) of 98%. This shows that the Problem Based Learning (PBL) learning model provides high effectiveness in improving student learning outcomes in mathematics subject matter of speed.